PELATIHAN PENCATATAN PEMBUKUAN SEDERHANA BAGI UMKM TERASI JEMBRET DI DUSUN KARANGMULYA - Sri Haryani; Tatik Yuniarti; Saepudin Saepudin (An-Nizam, 2022)
The problem that is often faced by the surrounding community, especially for Micro, Small and Medium Enterprises (MSMEs), is the difficulty in evaluating their business. Because many SMEs only focus on their business, they don't think about the importance of simple bookkeeping. The purpose of making this bookkeeping training is that students are expected to be able to channel some of their knowledge to be taught to MSMEs who do not understand how to do bookkeeping and MSMEs who are not familiar with bookkeeping in the preparation of simple financial reports, so that any problems that exist in MSMEs can be resolved and develop their business with a focus . . The implementation methods in bookkeeping training are: Socialization, Learning/Discussion, Training and Evaluation. Where this activity begins with socialization to MSMEs about the importance of bookkeeping, then a discussion session in the form of learning materials and guidance through videos is held followed by training in simple bookkeeping for MSMEs in Karangmulya Hamlet, Segarjaya Village. The results obtained from this activity are that the Terasi Jembret MSME actors have begun to understand simple bookkeeping training, and need to be carried out regularly so that it can be carried out better, and gives positive results knowing that the evaluation of their business experiences a gain or loss from recording profit financial statements. losses and can measure the ability of its business to be sustainable in the future.